Engineering Properties Of Asphalt Mixture Modified With Cup Lump Rubber - Lee, Zhi Zun (Universiti Sains Malaysia, 2021)
Recently, it is reported that the unstable global rubber price is due to over production from those rubber producing country. This is because the usage of the rubber internationally is less than the production of rubber from those rubber producing countries. Consequently, Government of Malaysia and industries had suggested a few approaches with purpose of increasing the domestic rubber usage within Malaysia. Hence, implementation of rubberized asphalt technology in the road construction currently had become main concern of the government. However, there are still have limited research, which is related to the performance of rubber modified asphalt. Consequently, this study will focus on how the addition of the cup lump will alter the original properties of the Conventional Asphaltic Mixtures in term of rutting resistance, resilient modulus as well as dynamic creep modulus. This study served a purpose to determine the suitability of the Cup Lump Rubber Modified Asphalt (CRMA) to replace the Conventional Asphalt (CA). In this study, two specimens were tested which are CA which acted as a control and CRMA. Initially, the Optimum Binder Content (OBC) for the asphalt was determined which are 4.57% and 5.22% for CRMA and CA respectively. Thus, the specimen that which are tested were prepared based on the OBC. The laboratory tests to be tested on the specimen were Hamburg Wheel Tracking test, Resilient Modulus test, and Dynamic Creep test. These tests were done to determine how the specimen reacted when loads are being applied to the specimen in different manners. Based on the results from the tests, CRMA performed 26.7% and 48.0% better than that of CA in resilient modulus and dynamic creep test. This is because the inclusion cup lump rubber had increased the elasticity and viscosity of the specimen. However, in the case of the Hamburg Wheel Tracking test, the rut depth of the CRMA is greater than that of the CA at 20,000 passes which is not what he had expected. However, the CRMA showed a better rutting performance initially or early stages. The densification of the CA took placed rapidly, and its rut depth reached to an optimum only after 2,000 passes approximately. On the other hand, densification of the CRMA took placed slowly which resulting its rut depth kept increasing and went beyond the rut depth of the CA after certain number of passes.